ChemInform Abstract: Multicomponent Reaction of Z‐Chlorooximes, Isocyanides, and Hydroxylamines as Hypernucleophilic Traps. A One‐Pot Route to Aminodioximes and Their Transformation into 5‐Amino‐1, 2, 4‐oxadiazoles by Mitsunobu—Beckmann Rearrangement. Issue 9 (February 2016) - Mercalli, Valentina; Massarotti, Alberto; Varese, Monica; Giustiniano, Mariateresa; Meneghetti, Fiorella; Novellino, Ettore; Tron, Gian Cesare
Abstract: A three‐component coupling reaction of Z‐chloro oximes, isocyanides, and hydroxylamine affords aminoglyoximes via [3+1] cycloaddition with preferential attack of isocyanides to nitrile N‐oxides.